The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.redox.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and apoptosis after acute respiratory hypoxia and reoxygenation in rat brain

Abstract: Acute hypoxia increases the formation of reactive oxygen species (ROS) in the brain. However, the effect of reoxygenation, unavoidable to achieve full recovery of the hypoxic organ, has not been clearly established. The aim of the present study was to evaluate the effects of exposition to acute severe respiratory hypoxia followed by reoxygenation on the evolution of oxidative stress and apoptosis in the brain. We investigated the effect of in vivo acute severe normobaric hypoxia (rats exposed to 7% O2 for 6 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
108
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 67 publications
(78 reference statements)
10
108
2
5
Order By: Relevance
“…The end products of the degradation of polyunsaturated fatty acids react with other lipids, thiol groups, amino groups of proteins, and nitrogenous bases of nucleic acids causing various effects, such as a change of antigenic protein properties, enzyme inactivation, and the inhibition of replication and transcription. 30 The human brain is composed of more than 60% lipids, and is particularly rich in membrane phospholipids with unsaturated fatty acid residues. Especially arachidonic acid and docosahexaenoic acid (DHA), which are the main source of polyunsaturated fatty acids in the brain, readily undergo peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The end products of the degradation of polyunsaturated fatty acids react with other lipids, thiol groups, amino groups of proteins, and nitrogenous bases of nucleic acids causing various effects, such as a change of antigenic protein properties, enzyme inactivation, and the inhibition of replication and transcription. 30 The human brain is composed of more than 60% lipids, and is particularly rich in membrane phospholipids with unsaturated fatty acid residues. Especially arachidonic acid and docosahexaenoic acid (DHA), which are the main source of polyunsaturated fatty acids in the brain, readily undergo peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria have numerous cellular functions including adenosine triphosphate (ATP) production, ROS production and sequestration, and control of apoptotic pathways (Flippo & Strack, 2017). Damage to the mitochondria can cause an imbalance in these processes resulting in decreased cellular energy production, increased ROS production, and apoptosis (Coimbra-Costa, Alva, Duran, Carbonell, & Rama, 2017;Fischer et al, 2016). Mitochondrial damage also impairs the cellular antioxidant system leading to oxidative stress.…”
mentioning
confidence: 99%
“…An unchanged glutathione content 4 days after hypoxia may suggest the recovery of cellular redox status. In the recent study of Coimbra‐Costa et al, it was shown that the oxidative damage induced by severe hypoxia in adult rats (7% O 2 , 6 h) is reversed 24 h of reoxygenation and the antioxidant activity and components of GSH antioxidant system returned to basal values at 24–48 h of reoxygenation, while the apoptotic events maintained at the 48 h post hypoxia (Coimbra‐Costa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular hypoxia and generation of ROS lead to accumulation of HIF1‐α and its translocation to the nucleus, but when the oxygen restores to normal level, HIF1‐α undergoes hydroxylation and proteasomal degradation (Dunwoodie, 2009; Perez‐Lobos et al, 2017). As the HIF1‐α is a marker of tissue hypoxia, increased HIF1‐α mRNA expression indicates the hypoxic status of an organism (Coimbra‐Costa et al, 2017; Coveñas et al, 2014). The elevated expression of HIF1‐α in hypoxic neonatal rats was previously shown in different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%